Effect of infant formula enriched with long-chain fatty acids and lutein on the formation of the central nervous system and vision from the standpoint of nutritional programming - I. N. Kholodova; E. S. Kiseleva; V. V. Nechaeva (Лечащий Врач, 2022)
The nature of nutrition from the moment of conception to the age of 24 months (the first 1000 days of life) is crucial for the development of the central nervous system and vision of the child. Therefore, formula-fed children need to receive nutrition that is not only rich in macro- and microelements, but also compensate for the possible deficiency of essential nutrients contained in breast milk. Although most infant formula contains all the necessary nutrients, this may not be enough for proper brain and vision development. Deficiency of long-chain polyunsaturated fatty acids and lutein, if it occurs during a period when there is a high need for certain nutrients necessary for the development of the central nervous system, can reduce the intensity of development of brain structures, the visual analyzer and affect the cognitive development of the child. Therefore, both nutrients are included in the regulatory documents as mandatory components of infant milk formula. Due to the limited bioavailability of long-chain polyunsaturated fatty acids and lutein from cow's milk, goat's milk-based formulas are a proven effective infant nutrition from birth that solves the problem of limited bioavailability of key essential nutrients.